Health sciences librarianship - Wood, M. Sandra (Medical Library Association books, 2014)
This comprehensive textbook of health sciences librarianship provides the library student and new librarian with the background and skills necessary to handle day-to-day activities and provide quality services in a health sciences library or a more general library serving students and practitioners in the health professions.